THE EFFECT OF PATIENT SATISFACTION AND TRUST ON THE INTEREST OF PATIENT REVISITS MEDIATED BY WORD OF MOUTH INTENTION AT THE MOM & BABY CLINIC MANGO BIG BRANCH - Mediana Sutopo Liedapraja; Hery Winoto Tj (Indonesian Interdisciplinary Journal of Sharia Economics, 2025)
This study analyzed the influence of patient satisfaction and trust on the interest in revisit by mediating word of mouth intention at the Mom & Baby Clinic in the Mangga Besar branch. The stagnation in the number of patient visits during 2023-2024, which only increased from 6,329 to 6,336 visits, far below the target of 8,000 visits, became the background of the study. With a quantitative approach, the study involved 130 respondents who were selected through purposive sampling. Hypothesis testing using the SEM-PLS method. The results showed that patient satisfaction and trust had a significant positive effect on word of mouth intention and interest in repeat visits. Patient trust had a more dominant influence (β=0.573) on word of mouth intention than satisfaction (β=0.243), while satisfaction had a stronger influence (β=0.291) on interest in repeat visits than trust (β=0.240). Word of mouth intention was shown to partially mediate the effect of satisfaction and fully mediate the influence of trust on interest in repeat visits. The findings indicate the importance of developing an integrated strategy that focuses on increasing patient trust as a determinant of word of mouth intention and patient satisfaction as a direct contributor to revisit interest.